Synergic Influence of Power Electronics, Electric Traction and Electro-Energetics - Branislav Dobrucky; Juraj Altus; Pavol Spanik (Communications - Scientific letters of the University of Zilina, 2001)
The contribution addresses the implementation of new progressive technologies in the field of electric traction in order to reduce feedback influence on the power network. First of all, it concerns Flexible Alternating Current energy Transmission Systems (FACTS), which, on the one hand, limit negative influence of the electric traction; on the other hand, they improve parameters of the power network by an electronic method. Taking their effects into account, the Power Active Filters (PAF) muddle through at most, because they allow compensation of fundamental harmonics, higher harmonics and also help to adapt energetic systems to Electromagnetic Compatibility (EMC) standards. Using the mentioned progressive technologies it is possible to achieve a higher value of effectiveness of electric energy transmission to a traction network.